Ecological aspects and sexual maturity of a southwestern Atlantic population of the planktonic shrimp Lucifer faxoni (Decapoda: Sergestoidea) - Alves Teodoro, Sarah de Souza [UNESP]; Farinelli Pantaleao, Joao Alberto [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP]; Costa, Rogério Caetano da [UNESP] (Crustacean Soc, 2014)
The demographic structure and morphological sexual maturity of the shrimp Lucifer faxoni Borradaile, 1915 are described here. The studied specimens came from Ubatuba Bay, in the north littoral of Sao Paulo State, Brazil. In each month of capture, 14 stations, 7 offshore and 7 inshore, were sampled with neuston nets during high tide periods. Relative growth was analyzed by observing the change in growth patterns of certain parts of the body in relation to somite length and total length (TL). Lucifer faxoni was most abundant in offshore regions. The relationship that best showed the size at the onset of the sexual maturity was the length of the 6th somite of the abdomen vs. TL. The external morphology of the petasma evidenced three development stages and such characteristic was also used to estimate sexual maturity for males using the P-50 technique. Our results show there is a preference of L. faxoni for offshore areas, probably explained by differences in abiotic factors. Both estimates of maturity (relative growth and petasma stage) were very similar. In this context, we propose the search for new structures for the analysis of the maturity of L. faxoni, thus promoting a wider study of what is related to the maturation of sergestoid shrimps.
Keywords: Brazilian coast; distribution; Luciferidae; neuston; tropical waters